Efeito do spray de delta 9-tetraidrocanabinol e canabidiol na mucosa bucal de ratos : avaliação clínica e histológica - Comunello, Iara Fiorentin (2020)
Nabiximols oromucosal spray, known under the commercial names Mevatyl® and Sativex®, comprises delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) for sublingual administration and has been prescribed to treat multiple sclerosis spasticity. Some adverse effects related to this therapy have been reported in the literature, including the occurrence of oral lesions. The aim of this study was to investigate the effects of nabiximols (Mevatyl®) on the oral mucosa. Thirty Wistar rats were allocated into two groups, according to the treatment received: (1) sublingual administration of Mevatyl® (n=15; THC/CBD group); (2) sublingual administration of ethanol/propylene glycol (n=15; vehicle group). Treatments were administered twice daily for 30 days. After that, the animals were clinically evaluated and euthanized. The floor of the mouth was surgically resected, and the overlying mucosa was examined by means of histomorphometry considering keratin thickness and the total thickness of the nucleated-cell epithelium. A qualitative histological analysis was also performed. The prevalence of oral lesion on clinical evaluation did not significantly differ between the groups. The vehicle group showed significantly greater keratin thickness than the THC/CBD group, but there was no significant difference for nucleated-cell epithelium thickness. Qualitative analysis results corroborated the histometric ones. Conclusion: Our data suggest the oral mucosal lesions reported as associated with nabiximols oromucosal spray are in fact associated with ethanol. THC/CBD seems to act as an antagonistic on the ethanol effects on the oral epithelium.